2015
DOI: 10.5978/islsm.15-or-11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stress-Free Therapy on immune system: Induction of Interleukin 10 expression in lymphocytes through activation of CD19(+) CD24(hi) CD38(hi) regulatory B Cells

Abstract: Background and aims:Mild thermal treatment with "Pinpoint Plantar Long-wavelength Infrared Light Irradiation (PP-LILI)" named as Stress-Free Therapy ® increases peripheral-deep body temperature and blood flow, and improves multiple disorders including hyperpiesia, type II diabetes and cardiovascular patients. Immunomodulatory effects of PP-LILI were investigated. Materials and methods: Seven healthy individuals and 4 people with underlying medical condition (UMC) participated in this study. Participants were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Furthermore, in view of the involvement of inflammatory cytokines (e.g., IL-6 and TNF-α) in DM, 12 SFT might have potential for contributing to the control of inflammation through activation of the immunoresponsive CD19 + CD24hi and CD38hi B-reg cell groups as well as IL-10 expression on lymphocytes. 9 We plan to conduct a more detailed future study focusing on these possibilities, including the relationships of SFT responses with dietary and exercise-related factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in view of the involvement of inflammatory cytokines (e.g., IL-6 and TNF-α) in DM, 12 SFT might have potential for contributing to the control of inflammation through activation of the immunoresponsive CD19 + CD24hi and CD38hi B-reg cell groups as well as IL-10 expression on lymphocytes. 9 We plan to conduct a more detailed future study focusing on these possibilities, including the relationships of SFT responses with dietary and exercise-related factors.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 We have additionally demonstrated that SFT activates the immunoresponsive CD19 + CD24hi and CD38hi B-reg cell groups and induces the expression of IL-10 on lymphocytes. 9 …”
Section: Introductionmentioning
confidence: 99%